CPU-Based Data Acquisition in Assessing the Impact of Inclination on Solar Panels - Youssef Rehouma; Boubaker Rouabah; Mohamed Mahboub; Mohamed Naoui; Zahra Djamaa (International Journal of Energetica)
A data logging system has been deployed to monitor two solar panels positioned at distinct inclination angles. This system records crucial parameters such as current, voltage, solar radiation incident on the panels, and panel temperatures. Comprising an Arduino microcontroller, a current sensor, a current and voltage sensor, and a Memory Card, the data logger captures and stores data in .txt files at 20-minute intervals. Employing a real-time acquisition system, the obtained results indicate that the data logger effectively archives and presents a wealth of information about solar panel characteristics. Notably, the data reveals superior performance of the solar panels at a 35-degree tilt angle compared to 32 degrees during April in the Ouargla region of Algeria.